TerraSAR-X and TanDEM-X observations of the Recovery Glacier system, Antarctica - Floricioiu, Dana; Abdel Jaber, Wael; Jezek, Kenneth (2014 IEEE Geoscience and Remote Sensing Symposium, 2014)
We analyzed ice velocities and surface elevations of the Recovery Glacier system in Antarctica derived from TerraSAR-X and TanDEM-X data. Our high resolution TerraSAR-X velocity mosaic was generated with speckle tracking applied to data acquired in 2012 and 2013 using the left looking mode. Flow variations along the main trunk of Recovery is discussed. In addition we processed 5 strips of TanDEM-X data from 2013 into calibrated DEMs. The Operation Icebridge ATM profiles crossing the main trunk of Recovery and the TanDEM-X elevation show very similar patterns confirming the capability of the SAR DEMs to provide spatially detailed topography of Antarctica.